2016
DOI: 10.1016/j.foreco.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and abiotic impacts of Double-crested cormorant breeding colonies on forested islands in the southeastern United States

Abstract: 13 (KC Hanson-Dorr), amanda.prisock@weyerhaeuser.com (AM Prisock), 14 brian.s.dorr@aphis.usda.gov (BS Dorr). 15 1 Tel.: +1 919 513 3312 16 2 Tel.: +1 662 325 5489 17 3 Tel.: +1 662 245 5250 18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 34 publications
0
35
1
1
Order By: Relevance
“…By abandoning dead and dying trees and selecting a living tree, the doublecrested cormorants tended to expand breeding sites (Hebert et al 2005). However, in this study area, the Lafferty et al (2016) reported that, although the ratio of live to dead trees used for nesting by the double-crested cormorant varied throughout the breeding area, in general, about 50% of the nest tree were dead. Further, 50% of the nest trees of the great blue herons (Ardea herodias) found breeding along with it were also dead.…”
Section: Discussionmentioning
confidence: 72%
“…By abandoning dead and dying trees and selecting a living tree, the doublecrested cormorants tended to expand breeding sites (Hebert et al 2005). However, in this study area, the Lafferty et al (2016) reported that, although the ratio of live to dead trees used for nesting by the double-crested cormorant varied throughout the breeding area, in general, about 50% of the nest tree were dead. Further, 50% of the nest trees of the great blue herons (Ardea herodias) found breeding along with it were also dead.…”
Section: Discussionmentioning
confidence: 72%
“…Cormorants have caused extensive damage to vegetation where they nest due to excessive guano, associated soil chemistry changes, and physical destruction (Hebert et al 2014;Ayers et al 2015;Lafferty et al 2016; Figure 5). These impacts can be relatively rapid (tree mortality in 3-10 years).…”
Section: Habitat and Co-nesting Speciesmentioning
confidence: 99%
“…Hebert et al (2014) documented significant damage to trees on forested islands associated with cormorant nesting and that vegetation damage can negatively impact co-nesting avian species that are obligate tree nesters. These impacts are not relegated to the cormorant's northern breeding grounds, as Lafferty et al (2016) documented significant impacts to trees and soils on southern breeding colonies. As the vegetation dies, the adaptable cormorant will often continue to nest on downed trees or the ground leading to open areas free of almost all vegetation.…”
Section: Habitat and Co-nesting Speciesmentioning
confidence: 99%
“…Namun, disisi lain keberadaan kelelawar menjadi salah satu daya tarik wisatawan karena dapat melihat kelelawar berukuran besar bergelantungan. Hal yang sama ditunjukan oleh Lafferty et al, (2016) yang menyebutkan bahwa keberadaan burung air yang bersarang di pucuk-pucuk pohon memberikan efek negatif terhadap kesehatan pohon tersebut. Namun keberadaan kelelawar juga memberi manfaat sebagai salah satu hewan penyebar biji, sebagai polinator, maupun pemangsa (Martins, 2017).…”
Section: Pengelolaan Yang Memadukan Kebutuhan Manusia Dengan Konservasiunclassified